COMPETITION-BASED GROUP QUIZ UNTUK LEARNING MANAGEMENT SYSTEM MOODLE - Ade Prayitno, “Prama; Oka Saputra, Komang; Ary Esta Dewi Wirastuti, Ni Made (Jurnal SPEKTRUM, 2022)
Quizzes are used by teachers in the learning evaluation process which aims to determine the extent of mastery of the material provided by the teacher to students. The quiz consists of several items about which are carried out directly by students. In this study, this research was carried out online by students in groups using a Learning Management System (LMS), namely Moodle with the help of a plugin. The result of the work is that the availability of the current score only produces 1 and then these values are to be developed for each student in the same group. This resulted in the evaluation process of learning in the quiz to be less fair Based on this problem, a plugin that can process is created that can process from work based on personal views generated by students. The personal score is then used to calculate the score by taking the average of all students in the group. Furthermore, the final value obtained from the calculation of the ratio of personal values to group values. This final score will be used to evaluate learning in the use of quizzes using Moodle. The results of the study after testing the system usability scale (SUS) showed that plugins that had good feasibility and blackbox testing methods declared the plugin well.